Understanding the Barriers to Collaborative Research: Experiences of Some Academics at the Zimbabwe Open University - Tarusikirwa, Moffat Chitapa (American Journal of Education and Learning, 2017)
Collaborative research is increasingly becoming popular with academics across the globe. There are many advantages that arise from research partnerships such as shared experiences in the form of research methodology, the pulling together of financial resources, research skills and technology among others. However, there are also many barriers to collaborative research. This research paper is based on the barriers to collaborative research as experienced by academics at the Zimbabwe Open University. The study employed a qualitative research approach. A purposive sample of 20 academics from the Zimbabwe Open University was used. Semi structured interview technique was used to gather data on the barriers to collaborative research. Interpretive content analysis was used for data analysis. Some of the barriers that were surfaced by the study include those to do with culture and language, different levels of experience in research, finance, research skills, and the inability to check research findings in different countries among others that will be discussed by the paper.